2015
DOI: 10.1080/09593330.2015.1058422
|View full text |Cite
|
Sign up to set email alerts
|

Stability and removal of atorvastatin, rosuvastatin and simvastatin from wastewater

Abstract: Atorvastatin (ATO), rosuvastatin (RST) and simvastatin (SIM) are commonly used drugs that belong to the statin family (lowering human blood cholesterol levels) and have been detected as contaminants in natural waters. Stability and removal of ATO, RST and SIM from spiked wastewater produced at the Al-Quds University campus were investigated. All three statins were found to undergo degradation in wastewater (activated sludge). The degradation reactions of the three drugs in wastewater at room temperature follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…This behavior is an accordance with a previous study concerning the degradation of ROS in aqueous solutions [20] [58,59]. The value of the apparent rate constant K app is found to be 0.32 min -1 (R² = 0.992) at 30 mA, 0.53 min -1 (R² = 0.998) at 60 mA, 0.55 min -1 (R² = 0.991) at 100 mA, and 1.02 min -1 (R² = 0.996) at 300 mA.…”
Section: Effect Of Applied Currentsupporting
confidence: 80%
See 1 more Smart Citation
“…This behavior is an accordance with a previous study concerning the degradation of ROS in aqueous solutions [20] [58,59]. The value of the apparent rate constant K app is found to be 0.32 min -1 (R² = 0.992) at 30 mA, 0.53 min -1 (R² = 0.998) at 60 mA, 0.55 min -1 (R² = 0.991) at 100 mA, and 1.02 min -1 (R² = 0.996) at 300 mA.…”
Section: Effect Of Applied Currentsupporting
confidence: 80%
“…Another study of degradation of rosuvastatin by wastewater treatment plants (WWTP) showed that the degradation rate in sludge was higher than in water because of the presence of many bacteria with a variety of enzymes Capable of catalyzing the processes of degradation of ROS. In addition, this treatment can cause secondary pollution of the environment [59]. Therefore, the present study investigates the performance of the EF process for the efficient removal of ROS.…”
mentioning
confidence: 99%
“…Recently, statins have been found to exert biological effects on osteoporosis, inflammation and other diseases in addition to their hypocholesterolemic activities [29][30][31]. Furthermore, several studies have shown that treatment with statins can reduce reproductive damage induced by hypercholesterolemia, however, the mechanisms by which obesity impairs spermatogenic function and how statins help recover from obesity-induced damage in the testes, sperm parameters, sex hormones, and metabolism is still unclear [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, these drugs including mevastatin were measured in wastewaters at concentrations such as 54.3 g L -1 , 21.6 g L -1 and 1.75 g L -1 on a daily basis [18]. The stability of atorvastatin, rosuvastatin and simvastatin drugs, which belong to the group of HMG-CoA reductase inhibitors (statins) similar to mevastatin was also published [24]. To investigate their removal from wastewater, activated sludge samples were designed to contain drugs at a concentration of 1 g L -1 [24][25].…”
Section: Resultsmentioning
confidence: 99%